Health Facility Surveys : An Introduction - Lindelow, Magnus; Wagstaff, Adam (World Bank, Washington, DC, 2014)
Health facility surveys come in various guises. One dimension in which they vary is their motivation. Some seek to understand better links between households and providers. Others seek to understand better provider behavior and performance. Still others seek to understand the interrelationships between providers, while yet others seek to shed light on the linkages between government and providers. Health facility surveys differ too in the data they collect, in part due to the different motivations. Surveys also vary in the way they collect data, some relying on direct observation, some on record review, and some on interview. Some quality data are collected through clinical vignettes. Facility data have been put to a variety of uses, including planning and budgeting; monitoring, evaluation, and promoting accountability; and research. Lindel and Wagstaff review some of the literature under each heading and offer some conclusions regarding the current state of health facility surveys.